2009
DOI: 10.1016/j.jhydrol.2009.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Trends in flood magnitude, frequency and seasonality in Germany in the period 1951–2002

Abstract: 21During the last decades several destructive floods in Germany led to the impression that 22 the frequency and/or magnitude of flooding has been increasing. In this study, flood 23 time series are derived and analyzed for trends for 145 discharge gauges in Germany. A 24 common time period of 52 years ) is used. In order to obtain a country-wide 25 picture, the gauges are rather homogeneously distributed across Germany. Eight flood 26 indicators are studied, which are drawn from annual maximum series and peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
197
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(211 citation statements)
references
References 39 publications
8
197
1
5
Order By: Relevance
“…Moreover, significant upward trends were observed in several gauge records by Jeong et al (2008) after they have investigated trends in the peak flood data for the major Korean river basins. Petrow and Merz (2009) analysed the trends in the flood data in Germany using MK test. The analysis detected significant flood upward trends for a considerable fraction of basins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, significant upward trends were observed in several gauge records by Jeong et al (2008) after they have investigated trends in the peak flood data for the major Korean river basins. Petrow and Merz (2009) analysed the trends in the flood data in Germany using MK test. The analysis detected significant flood upward trends for a considerable fraction of basins.…”
Section: Introductionmentioning
confidence: 99%
“…In this case large areas can be protected in flood plain, upstream and local inflows, which percent can put together up to 50 % on the part of total inundated area in the river basin, due to spatial distribution of flood protection regulating reservoir. This approach accords with modern strategy of flood risk decreasing by management of flood discharge for all river basins by distributed system of DWRs with minimal impact on the environment [14,15].…”
Section: Methodsmentioning
confidence: 73%
“…Hydrological mean and low flow time series "may frequently display statistically significant serial correlation" (Yue et al, 2002). To account for this, the procedure of trend-free-pre-whitening was applied, which consists of 5 steps and is described in detail in Yue et al (2002) and Petrow and Merz (2009): first, linear trends are estimated for all time series, applying a robust slope estimator (after Sen, 1968, cited in Petrow andMerz, 2009). The linear trend is removed from the series in a second step by subtraction of the trend value in each time step.…”
Section: Trend Analysismentioning
confidence: 99%
“…Stahl et al, 2010;Kundzewicz et al, 2005;Svensson et al, 2005;Lindström and Bergström, 2004;Robson, 2002). For Germany, Petrow and Merz (2009) found that flood events in 50-year runoff time series of several macroscale catchments reveal positive trends, especially in winter. Within the cooperation project KLIWA, changes in mean flow and hydrological extreme events in southern German catchments have been assessed.…”
Section: Introductionmentioning
confidence: 99%